Comparison of Smoking Habits and Coffee Consumption In Adolescents Against Hemoglobin Levels In Mojoroto Kediri City: Perbandingan Kebiasaan Merokok dan Mengkonsumsi Kopi Pada Remaja Terhadap Kadar Hemoglobin Di Mojoroto Kota Kediri - Purnadianti, Mely; Ermawati, Nita; Berlian , Rere Nadhif (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Cigarettes are processed tobacco using or without addictive substances. The increasing of hemoglobin in smokers due to the content of carbon monoxide causes hemolysis of erythrocytes that is stronger than oxygen, so that hemoglobin increases. In addition to smoking, the society's habit is about coffee consumption. Coffee is a beverage with high polyphenols. The decreasing of hemoglobin occurs when drinking too much coffee. It will reduce the absorption of iron and erythrocytes ability to deliver oxygen from the lungs to all tissues in the body, therefore the hemoglobin will decrease. One of the laboratory tests that is used to see hemoglobin levels in smokers and coffee consumers is the POCT method of hemoglobin examination. The purpose of this study was to analyze the comparison of the effect between smoking and coffee consumption on hemoglobin levels in adolescents on the streets of Mejenan Gang 3 Mojoroto Kediri. The method that is used in this research is comparative study and the sampling technique that is used purposive sampling with a sample size of 40 respondents. The results show that 10 adolescents (50%) had abnormal hemoglobin levels and 10 adolescents (50%) had normal hemoglobin levels. 5 teenagers (25%) had abnormal hemoglobin levels and 15 (75%) normal hemoglobin levels. Based on statistical tests, the results obtain p-value 0.423 and> 0.05. So it can be concluded that there is a moderate effect between cigarettes and coffee on hemoglobin levels in adolescents on Mejenan Street Gang 3 Mojoroto Kediri.